Implementation of Protection Services for Women and Children Victims of Violence at Daerah Istimewa Yogyakarta: An Institutional - Muhammad Khozin; Nur Faidati; Gerry Katon Mahendra (Iapa Proceedings Conference, 2020)
Cases of violence against women and children in Daerah Istimewa Yogyakarta (DIY) in 2019 has reached 1,469 cases. This condition requires a special attention from the Government. The implementation of protection services for women and children victims of violence in DIY is carried out by P2TPAKK "Rekso Dyah Utami". This institution has been established and served the community since 2004. However, the existence of P2TPAKK "Rekso Dyah Utami" began to be interrupted by the Regulation of the Minister of Women Empowerment and Child Protection of the Republic of Indonesia No. 9 of 2016 on Guidelines for the Nomenclature of Regional Apparatus in the Field of Women Empowerment and Child Protection which mandates that service providers for the protection of women and children victims of violence must take the form of Technical Service Unit (UPTD). This raises a dilemma for the DIY government. Then, what is the suitable institutional format for the implementation of the service for DIY government? This study employed a qualitative approach with data collection techniques using a desk study and a FGD. The parties involved in this FGD were the Office of Women Empowerment of DIY, P2TPAKK "Rekso Dyah Utami", and other stakeholders. The data were analyzed through descriptive qualitative and SWOT analysis. The study revealed that the service delivery was well established. However, the SWOT analysis found that there were still a number of problems that were not recognized by the central government as an institution. Therefore, to keep the services to the community, the DIY government is recommended to form an UPTD structure and organizational’s resources engineering.